Policy Strategy to Stimulate Indonesia’s Palm Oil Downstream Industries - Yulia Setia Lestari; Muzzar Kresna; Nur Hadiati Endah; Nailatalmuna Nitrasatri Atmaja; Eristya Puspitadewi Irwanto; Brian Pratistha (Pusbindiklatren Bappenas, 2025)
The Indonesian government has prioritized downstream industrial development to enhance the economic value of domestically produced palm oil. This initiative targets three strategic sectors: oleo-food, oleochemicals, and bioenergy. The advancement of these industries entails more than an expansion of upstream production; it requires a nuanced understanding of each sector’s absorption and production capacities. This study employs the Analytic Hierarchy Process (AHP) to assess investment characteristics and competitiveness within these downstream sectors. The findings identify six critical policy factors to stimulate investment: tax incentives, the establishment of special economic zones, improved plantation productivity, favorable pricing for fresh fruit bunches (FFB), enhanced access to agroindustrial financing, and the integration of upstream and downstream operations. These elements are essential for fostering a conducive investment climate and advancing the transformation of Indonesia’s palm oil sector to support broader national economic development goals.